Legal Protection for Borrowers for Agreements with Standard Clauses on Implementation Fintech Lending - Wibiantoro, Donny Yuhendra; Mahanani, Anajang Esri Edhi (Fakultas Hukum Universitas Widya Mataram, 2023)
The purpose of this study is to explore legal protection for loan recipients for agreements with standard clauses in implementationfintech. The research method is normative juridical, with a statutory and conceptual approach. The results of the study show that legal protection in standard agreements shows that it has not been realized properly, this is because there are principlestake it or leave it which then set aside the legal norm in the form of the principle of freedom of contract. Besides, there is no embodiment of the principle of consumer protectionfintech lending, namely transparency and complaint service mechanisms. The legal remedies in the agreement tend to prioritize repressive efforts and override preventive measures by not providing education about the complaint mechanism. which leads to injustice for the recipient of the loan. Keywords: Legal Protection, Fintech Lending, Standard Agreement.